2012
DOI: 10.1515/jpm-2012-0026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal vitamin A deficiency during pregnancy on neonatal kidney size

Abstract: Maternal VAD during pregnancy may decrease renal size in the infant at birth. The functional implications of this effect warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
3
24
1
1
Order By: Relevance
“…97 A similar finding was reported among Indian and Egyptian infants, where a reduction in kidney size was associated with reduced maternal vitamin A levels (Supplementary Table 1). 98,99 Supplementation with vitamin A during gestation rescued the nephron number in rats with LBW, but a study in preterm baboons did not show an effect on nephrogenesis. 81,100 Numerous studies have demonstrated that maternal vitamin A supplementation in regions where vitamin A deficiency is common has no effect on birth weight, blood pressure, or microalbuminuria in childhood; such supplementation is, however, associated with improved neonatal and infant survival (Supplementary Figure 1 and Tables 2 and 3).…”
Section: Maternal Micronutrient Deficienciesmentioning
confidence: 95%
“…97 A similar finding was reported among Indian and Egyptian infants, where a reduction in kidney size was associated with reduced maternal vitamin A levels (Supplementary Table 1). 98,99 Supplementation with vitamin A during gestation rescued the nephron number in rats with LBW, but a study in preterm baboons did not show an effect on nephrogenesis. 81,100 Numerous studies have demonstrated that maternal vitamin A supplementation in regions where vitamin A deficiency is common has no effect on birth weight, blood pressure, or microalbuminuria in childhood; such supplementation is, however, associated with improved neonatal and infant survival (Supplementary Figure 1 and Tables 2 and 3).…”
Section: Maternal Micronutrient Deficienciesmentioning
confidence: 95%
“…122 Vitamin A is an important regulator of cell proliferation and differentiation and plays a critical role in the determination of nephron mass. [123][124][125] Vitamin A deficiency is also common in premature infants 126 due in part to increased urinary losses of vitamin A. 127 Although vitamin A supplementation appears to be beneficial in the lung, another branching organ that develops in late gestation, in protecting against chronic lung disease, 128 there are no clinical data on renal outcomes in humans.…”
Section: Research Horizons Nephrogenesismentioning
confidence: 99%
“…This explains why the retinol of newborns from deficient mothers is in the majority of studies inferior to that of newborns born to non-deficient mothers [12]. This finding was also observed in Vitamin A deficiency during pregnancy is associated with a rise in maternal and infant mortality and morbidity and mortality in the first year of life.…”
Section: Discussionmentioning
confidence: 78%
“…In India, Radhika et al found that 27% of women have Vitamin A deficiency in a population of 736 pregnant women [11]. In Egypt, in a study of a population of 80 mother-child pairs, 20% of mothers had Vitamin A deficiency and a significant difference between mean retinol of newborns from deficient mothers and those from non-deficient mothers [12]. In Egypt, Hamdy et al found a proportion of 23.5% of pregnant women with a low rate of Vitamin A in a population of 736 with a positive correlation with the rate of Vitamin A of newborns [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation